Labyrinthine Fistula Secondary to Cholesteatomatous Chronic Otitis Media - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2010)
Objective: To analyze clinical presentation, preoperative diagnostic methods, surgical treatment and postoperative outcomes of labyrinthine fistula (LF) secondary to cholesteatomatous chronic otitis media. Materials and Methods: Of 582 mastoid surgeries performed, a retrospective review of 33 patients with LF secondary to cholesteatomatous chronic otitis media was performed. Setting: Tertiary referral center. Interventions: Audiologic evaluation with pure tone bone conduction average (PTA-bone) and radiologic imaging studies with temporal bone computed tomography (CT) scanning were evaluated. Open technique with a removal of the cholesteatoma matrix and sealing the fistula site with connective tissue was preferred. Main outcome measures: Auditory results were evaluated as a function of LF size and site. Results: Incidence of LF was 5.7 % (n:33). Isolated fistula of the lateral semicircular canal was found in 25 patients (75.7%), and isolated involvement of the oval window was found in one patient (31%). Multiple fistulas were detected in 7 patients (21.2%). In 31 patients (88.2%), the cholesteatoma was completely removed, and the fistula was sealed; and in 2 patients (5.8%) the matrix was left intact after exteriorization. One patient (3%) presented with anacusis. Postoperatively, hearing remained in the same range in 24 patients (72.7%). In 8 patients (24.2%) a reduction of PTA-bone was observed, and 2 patients (6%) presented with postoperative anacusis. Vertigo improved or disappeared in 14 (42.4%) cases, and remained unchanged in 4 (12.1%) cases. Conclusion: LF is an aggressive complication of cholesteatomous chronic otitis media. The postoperative prognosis is correlated to the size and location of the LF.
Keywords: EAR SURGERY; MANAGEMENT; COMPLICATIONS